Structured Training and Labor Productivity in Small Businesses in Uzbekistan - Egamberdieva Barnakhon Gulamjanovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Small businesses are fundamental to economic development, particularly in emerging economies, due to their capacity for job creation and innovation. Specific Background: In Uzbekistan, government reforms have increasingly prioritized SME development through policies promoting entrepreneurship and labor enhancement. Knowledge Gap: Despite their significance, limited research explores how labor potential—defined by productivity, training, and retention—affects small business growth in this context. Aims: This study investigates the relationship between labor potential and economic performance in small businesses, focusing on workforce development strategies and the impact of national policy measures. Results: Quantitative and qualitative data from 200 SMEs and 40 interviews revealed a strong correlation (ρ = 0.82) between structured training and revenue growth, while low turnover was linked to higher efficiency. Government-supported initiatives, such as the “One Million Entrepreneurs” program, significantly enhanced labor outcomes. Novelty: The research uniquely integrates firm-level data with an analysis of policy frameworks in Uzbekistan, offering sector-specific insights and documenting tangible returns on labor investment. Implications: Findings underscore the necessity of public-private collaboration in strengthening SME labor potential, providing a replicable model for workforce-driven growth in other developing countries.HIghlight : Training Boosts Growth: Structured employee training is linked to 30% higher productivity and 15% revenue growth. Turnover Hurts Performance: Businesses with low employee turnover saw 20% more revenue growth. Policy Support Matters: Uzbekistan's government-backed training and tax incentives significantly improved SME productivity. Keywords : Small Businesses, Labor Potential, Productivity, Training Programs, Uzbekistan